2007
DOI: 10.1097/01.bsd.0000211285.91271.b3
|View full text |Cite
|
Sign up to set email alerts
|

Septic Arthritis of Lumbar Facet Joints Without Predisposing Infection

Abstract: Septic arthritis of a lumbar facet joint is a rare clinical entity and most articles have reported a single case. There have been few studies that have evaluated the clinical and imaging features of septic arthritis of lumbar facet joints. The clinical data of 5 patients diagnosed with septic arthritis of lumbar facet joints were retrospectively studied. The average age of 5 patients was 73.6 years. All patients had elevated temperature at admission (37.7 degrees C). Leukocyte count was tested in all 5 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
0
21
0
7
Order By: Relevance
“…The pathophysiology of the epidural abscess is explained because of the narrow facet joint cavity, which facilitates the easy spread of infection to the epidural space (by rupture of the ventral aspect of the joint capsule) and to the paravertebral muscles (by rupture of the posterior aspect of the joint capsule) [1,10]. Another mechanism of physiopathology of hematogenous spread to the extra facet has been reported in some studies [4,5]. For example, Muffoletto et al stated that hematogenous spread occurs via the branches of the posterior intercostal vessels [4].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The pathophysiology of the epidural abscess is explained because of the narrow facet joint cavity, which facilitates the easy spread of infection to the epidural space (by rupture of the ventral aspect of the joint capsule) and to the paravertebral muscles (by rupture of the posterior aspect of the joint capsule) [1,10]. Another mechanism of physiopathology of hematogenous spread to the extra facet has been reported in some studies [4,5]. For example, Muffoletto et al stated that hematogenous spread occurs via the branches of the posterior intercostal vessels [4].…”
Section: Discussionmentioning
confidence: 98%
“…Septic arthritis of the facet joint is a rare condition. Four retrospective reviews of case reports in the literature found that septic arthritis of the facet joint causes 4%-20% of pyogenic spinal infections, 86%-97% of which occur in the lumber spine [3][4][5][6]. It has been reported that there are some risk factors that predispose to infection in PFJI patients, but Narváez et al have stated that more than 60% of PFJI patients show no systematic risk factors, indicating that spontaneous PFJI can also affect immune-competent patients, as was seen in our case [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34][35] This is another important route of infection resulting in epidural/ paraspinal abscesses. Facet joint infection is often haematogenous but also caused by epidural anaesthesia and spinal procedures.…”
Section: Epidural/paraspinal Abscess With Facet Joint Infectionmentioning
confidence: 99%